Pengaruh Sistem Informasi Pemasaran dan Distribusi Terhadap Efektivitas Penjualan Pada PT Suryamas Lestari Prima Tanjung Morawa - Abdurrahman Siregar; Ronda Deli Sianturi (Forum Kerjasama Pendidikan Tinggi, 2021)
The purpose of this study is to describe marketing information systems and distributions are implemented in improving the effectiveness of sales at PT. Suryamas Lestari Prima Tanjung Morawa, to describe the resistant barriers in decision-making on distribution and to describe the effect of marketing and distribution services. From t test obtained t count = 5,686, while ttable value at n-2 (36 - 2) that is 34 at significant level 5% ttable equal to 2,04, and if t arithmetic> ttable then alternative alternative (Ha) accepted, the existence of significant influence between marketing information service and distribution to sales effectiveness in PT. Suryamas Lestari Prima Medan. From rx1y = 0.624, rx2y = 0.687, rxix2 = 0.798, The reaction result is rxix2y = 0.698, and when compared to rtabel at n = 36 with 5% significant level that is 0,329 bigger rhitung> rtabel. Thus it is certain to be accepted as proven. Thus the test of Fasil Fcount (Fh) = 15.690 is then consulted with Ftabel, with built on the dk of the numerator = k and dk denominator = (n-k-1), the result Ftable = 3.28. The result shows that F count is greater than Ftable that is 15.690> 3.28 then that is two significant things. Percentage of influence between independent variable (x1) that is marketing information system and independent variable (x2) that is with dependent variable (y) to sales effectiveness in PT. Suryamas Lestari Prima Medan 48.7% while 51.3% by other factors beyond the contribution of this study. An integrated marketing information system development plan in the near future soon commencement and existing computer capacity.